Endogenous Testosterone and Exogenous Oxytocin Modulate Attentional Processing of Infant Faces - Holtfrerich, Sarah K. C. (PLoS One, 2016)
Evidence indicates that hormones modulate the intensity of maternal care. Oxytocin is known for its positive influence on maternal behavior and its important role for childbirth. In contrast, testosterone promotes egocentric choices and reduces empathy. Further, testosterone decreases during parenthood which could be an adaptation to increased parental investment. The present study investigated the interaction between testosterone and oxytocin in attentional control and their influence on attention to baby schema in women. Higher endogenous testosterone was expected to decrease selective attention to child portraits in a face-in-the-crowd-paradigm, while oxytocin was expected to counteract this effect. As predicted, women with higher salivary testosterone were slower in orienting attention to infant targets in the context of adult distractors. Interestingly, reaction times to infant and adult stimuli decreased after oxytocin administration, but only in women with high endogenous testosterone. These results suggest that oxytocin may counteract the adverse effects of testosterone on a central aspect of social behavior and maternal caretaking.